Estimation of Gender wage Discrimination in the Portuguese labour market - Amélia Bastos; Graça Le\~ao Fernandes; José Passos (European Regional Science Association (ERSA), 2003)
Gender wage discrimination is a reality in the Portuguese labour markets although no study has been until now carried on to measure its dimension. We think that economists should contribute to the knowledge of the dimension and significance of this phenomenon by giving orientation for the definition of political measures towards its reduction. In this paper we measure the size of gender wage discrimination in the Portuguese labour market. Furthermore, we evaluate this measure for the five Portuguese main regions. In recent literature about the measurement of gender wage discrimination the Oaxaca decomposition and its developments is a commonly used approach. We extend this approach using bootstrap techniques for statistical inference purposes.
Keywords: 330